Morphological and phenological characteristics of leaf development of Durio zibethinus Murray (Bombacaceae) - Ogawa, Kazuharu; Furukawa, Akio; Hagihara, Akio; Abdullah, Ahmad Makmom (Springer-Verlag, 1995)
The morphological and phenological characteristics of leaf development of Durio zibethinus Murray were investigated at an experimental field of Universiti Pertanian Malaysia (UPM) in Selangor. Proportionality was observed in the relations of leaf length to leaf width and of leaf area to the product of leaf width and length. The proportionality was explained from the similarity of leaf shape. New leaves emerged continuously, but the number of new leaves fluctuated seasonally. The emergence of leaves was inhibited by the flower bud formation. In the survival curves of leaves, the relative fall rate was lower at the early stage of leaf development than at the late stage. Leaf longevity of 100 to 133 days was low and leaf expansion period of two weeks was short in comparison with the published data on tropical trees. From the ecophysiological viewpoint, the leaf survival strategy of the present species was discussed: the present species manages to set up a photosynthetic system in a short period by the rapid leaf growth; the lower leaf longevity is advantageous to reaching more frequently high photosynthetic production by newly emerged leaves. © 1995 The Botanical Society of Japan.